Identifikasi Citra Daun Menggunakan Morfologi, Local Binary Patterns dan Convex Hulls - Prasvita, Desta Sandya (LPPM of STIMIK ESQ, 2016)
This research proposes a leaf identification system with features fusion of leaf morphology, convex hulls (shape features) and